Buy coal for preservation and act strategically on the fuel market - Rüdiger Pethig; Thomas Eichner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In Harstad's (2012) model, climate damage only hits one group of countries, called the coalition, and the coalition's climate policy consists of capping own fuel de- mand and supply combined with the purchase of fossil fuel deposits for preserva- tion. Harstad's Theorem 1 states that if the deposit market clears the coalition's strategic fuel-cap policy implements the first-best. The present paper reconstructs that efficiency result and argues that the deposit market equilibrium as defined in Harstad (2012) fails to be attained, unless the non-coalition countries act cooper- atively on the deposit market. Without such cooperation, the coalition's strategic action on the fuel market distorts the allocation to its own favor.
Keywords: Q31; Q38; Q54; 330